When the farm-gate becomes a revolving door: An institutional approach to high labour turnover. (December 2017) - Staelens, Lotte; Louche, Céline
By adopting an institutional theory lens, the aim of the article is to better understand the actions and mindset of managers toward high labour turnover in the cut-flower industry in Ethiopia. Our mixed-method approach explores the ways in which managers deal with, and legitimize, high levels of labour turnover. Our results show that they engage in three types of practices – predicting, containing and accommodating – whose objective is to make labour turnover tolerable, rather than reduce it. Interestingly, managers do not legitimize their practices through the use of cost-benefit arguments, as the literature would have suggested, but blame the institutional context. This article highlights the context-dependent aspects of labour turnover and explains how managers may find themselves in a deadlock situation. It informs the debate in human resource management research about managerial practices at the bottom of global value chains.